Health interprofessional collaborative practice in exclusive breastfeeding: a scoping review - Arista Kusuma Wardani; Sulistyaningsih Sulistyaningsih; Nurul Mahmudah (International Journal of Health Science and Technology, 2021)
The iWorld iHealth iOrganization ireports ithe ilow icoverage iof iexclusive breastfeeding. iThe ineed ifor icollaborative ipractices iof iinterprofessional ihealth ias an ieffort ito iincrease iexclusive ibreastfeeding icoverage. iThe ipurpose iof ithis scoping ireview iis ito ianalyze ithe ihealth iinterprofessional icollaborative ipractice in exclusive ibreastfeeding. iThis iscoping ireview iused ithe iArksey iand iO'Malley framework. iSearch ifor iarticles ipublished ifrom i2009 ito i2019 ifrom i5 idatabases (PubMed, iWiley, iSciencedirect, iEBSCO, iand igoogle ischolar). iData iwere reviewed using ithe iPRISMA iflowchart. iThe iresults iof ithe ireview ifound ithe irole iof ihealth professionals iand ihealth iinterprofessional ibarriers iin iexclusive ibreastfeeding.